Desenvolvimento local no Estado do Amapá: a contribuição do Instituto Federal de Educação, Ciência e Tecnologia do Amapá (IFAP) nos municípios de Macapá e Laranjal do Jari - PASCHOALIN, Karina Pingarilho (Universidade Federal do Pará, 2024)
This research evaluated the role of the Instituto Federal de Educação do Amapá (IFAP) in the local development of the municipalities of Macapá and Laranjal do Jari, focusing on educational, economic and social aspects, based on the theory of endogenous local development. The importance of this study resides in the need to understand the impact of educational institutions, such as IFAP, in promoting socioeconomic development and improving the quality of life of local communities. The study methodology involved quantitative and qualitative analyses, using secondary data, bibliographical research and questionnaires. Information sources included socioeconomic, educational, and demographic indices. The research compared the FIRJAN Index of Macapá and Laranjal do Jari before and after the implementation of the IFAP. Thus, it was possible to achieve the objective of the work, which was to analyze the contribution of IFAP in the local development of Macapá and Laranjal do Jari, proposing an integrative extension project. The results showed a significant increase in the Firjan Index in both cities, being higher in Laranjal do Jari (16.3%) compared to Macapá (5.1%). In addition, the survey revealed improvements in local infrastructure. The community values IFAP for providing job opportunities, professional training and integral development. The study concludes that the implementation of the IFAP campuses contributed to the local development of the municipalities of Amapá, confirming the objective of the research. This work hopes to encourage new research and debates on the importance of Professional and Technological Education. In addition, it is expected that this study will contribute to the expansion and improvement of public policies aimed at the integration between academic training and the labor market, promoting an emancipatory teaching and learning process that benefits local communities.